2021
DOI: 10.1186/s12944-021-01604-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep apnea syndrome on the altered lipid metabolism and the redox balance

Abstract: Background Obstructive sleep apnea (OSA) is a disorder with a significant risk for cardiovascular diseases. Dyslipidemia and redox imbalance belong to potential mechanisms linking OSA with the development of vascular diseases. The main aim of this study was the evaluation of the presence of lipid abnormalities in OSA patients, focusing on small dense low-density lipoprotein (LDL) and high-density lipoprotein (HDL) subfractions and determination of the redox imbalance by evaluating the marker of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
(44 reference statements)
0
20
1
Order By: Relevance
“…The selected studies in this study were verified to have no publication bias, and sensitivity analysis also showed that the results of this study were relatively stable [ 25 ]. Therefore, it can be considered that the effect of this study is relatively reliable.…”
Section: Discussionmentioning
confidence: 97%
“…The selected studies in this study were verified to have no publication bias, and sensitivity analysis also showed that the results of this study were relatively stable [ 25 ]. Therefore, it can be considered that the effect of this study is relatively reliable.…”
Section: Discussionmentioning
confidence: 97%
“…Several modified LDL particles were identified, such as oxidised LDL (oxLDL), small dense LDL (sdLDL) and desialylated LDL, which are strongly atherogenic [ 28 , 29 , 30 ]. Further subclasses can be identified by gel electrophoresis: large (LDL 1–2) and small (LDL 3–7) subfractions [ 31 ]. Circulating LDL particles are absorbed by the liver (70%) and peripheral tissues (30%), mainly by the LDL receptor (LDLR) [ 32 ].…”
Section: Overview Of Physiological Lipid Metabolismmentioning
confidence: 99%
“…These can further be divided into HDL3c, HDL3b, HDL3a, HDL2a and HDL2b fractions [ 57 ]. Further subclasses can be identified by gel electrophoresis: large (HDL 1–3), intermediate (HDL 4–7) and small (HDL 8–10) subfractions [ 31 ]. The small HDL 8-10 particles are atherogenic through easy penetration to the endothelium and low recognition by HDL receptors [ 59 , 60 ].…”
Section: Overview Of Physiological Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed a significant correlation of HDL with OSA severity, indicating that patients with lower HDL values have higher Apnea-Hypopnea Index (AHI). Considering protective cardiovascular effects of high-density lipoproteins (HDL), it is shown that certain subfractions of HDL, especially small HDL subfractions including small LDL3–7 and small HDL8–10, can have atherogenic effects in patients with OSA ( Kollar et al, 2021 ). On the other hand, bigger HDL subfractions can have impaired antioxidant activity because of increased HDL lipid peroxide levels and decreased serum paraoxonase-1 (PON1) activity, which are the two main factors related to the antioxidant activity of HDL ( Yadav et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%